The artistic world of Shulamite and The Star of Solomon by A. I. Kuprin: between neorealism and postmodernism - Краснова, Анастасия Александровна; Московкина, Ирина Ивановна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article describes the specifics of A. I. Kuprin’s tales Shulamite and The Star of Solomon (the play with the images of his own and the images of somebody else’s; the consistent demythologization of pretexts and the creation of “new myths” similar to the symbolistic ones; the dilution of the borders between sleep and reality; the intensification of the ironic and playing principles, etc.) proving that the writer’s neorealism is open to the modernistic experience and that elements of pre-postmodernism are formed. This makes the views of the A. I. Kuprin’s innovations and his place in the literary process of the “Silver Age” more accurate.